2019
DOI: 10.1136/injuryprev-2018-043117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a cognitive test at license renewal for older drivers on their crash risk in Japan

Abstract: ObjectiveTo evaluate the effect of adding a cognitive test to a license renewal procedure for drivers aged 75 years or older in reducing their motor vehicle collisions (MVCs). The test has been obligatory since June 2009.MethodsUsing monthly police-reported national data on MVCs from January 2005 through December 2016, we calculated the rates of MVCs per licensed driver-year by sex and age group (70–74, 75–79, 80–84 and 85 years or older) for each month together with the ratios of MVC rates of drivers in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 17 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…In developed countries, the number of traffic accidents caused by older drivers is increasing over time, along with the aging population. In Japan, the number of licensed drivers aged over 65 years has increased in recent years, exceeding 18 million in 2018, and the number of fatal accidents caused by older drivers has maintained an upward trend (Ichikawa et al, 2020). Although previous studies consistently showed that individuals with dementia are at increased risk of unsafe driving among the older population (Drachman and Swearer, 1993;Frittelli et al, 2009), surprisingly, a report published by the National Police Agency revealed that approximately half of the older drivers who caused fatal accidents were cognitively normal (National Police Agency, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, the number of traffic accidents caused by older drivers is increasing over time, along with the aging population. In Japan, the number of licensed drivers aged over 65 years has increased in recent years, exceeding 18 million in 2018, and the number of fatal accidents caused by older drivers has maintained an upward trend (Ichikawa et al, 2020). Although previous studies consistently showed that individuals with dementia are at increased risk of unsafe driving among the older population (Drachman and Swearer, 1993;Frittelli et al, 2009), surprisingly, a report published by the National Police Agency revealed that approximately half of the older drivers who caused fatal accidents were cognitively normal (National Police Agency, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…of a benefit of mandatory age-based screening policies on the safety of elderly drivers could be demonstrated [2][3][4][5][6][7].…”
Section: Figurementioning
confidence: 99%
“…Other studies, however, have observed negative effects: one study found higher fatality rates among pedestrians and cyclists in Finland (with agebased screening policy) compared with Sweden (no such policy) [10]. Two studies found higher injury and mortality rates of pedestrians and cyclists, respectively, after a cognitive test was added to the existing licensing renewal procedure [6,9]. It is hypothesised that elderly persons who have had their driver's licence revoked or voluntarily handed it in due to the screening procedure may switch to the unprotected modes of transport, which are significantly less safe for them [2,8].…”
Section: Seriously or Fatally Injured Pedestrians And (E-)cyclistsmentioning
confidence: 99%
See 2 more Smart Citations